1968
DOI: 10.1007/bf00430102
|View full text |Cite
|
Sign up to set email alerts
|

Labilit� structurale des granules de s�cr�tion contenant du zinc des cellules ? du pancr�as apr�s gazage avec de l'hydrog�ne sulfur�

Abstract: Summary. Treatment of vertebrate pancreatic islet tissue with hydrogen sulphide, thus initiating the sulphidesilver procedure for ultrastructural visualization of heavy metals in tissues, evoked marked swelling in zinc-containing secretion granules of fl-cells in several species rapidly leading to disruption of many granules. Other organelles of the fi-cells were unaffected, as also were the secretion gramfles of adjacent zinc-containing ~2-cells. Likewise, fiand ~2-granules with no heavy metals or only traces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1969
1969
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Besides a more compact packaging of insulin in the secretory granules, zinc‐insulin crystallization is also believed to protect insulin against proteolytic degradation 58,59 . However, several data argue against this idea: (i) the presence of an intact 5808 Da insulin peptide as one sharp mass peak in the spectrum of islets of both wild‐type and ZnT8 −/− mice, measured by in situ peptidomics 26 ; and (ii) the non‐crystallized guinea pig and coypu insulin would be more vulnerable to degradation, compared with human crystallized insulin 60,61 .…”
Section: Role Of Znt8 In Insulin Processing and Storage: Formation Ofmentioning
confidence: 99%
“…Besides a more compact packaging of insulin in the secretory granules, zinc‐insulin crystallization is also believed to protect insulin against proteolytic degradation 58,59 . However, several data argue against this idea: (i) the presence of an intact 5808 Da insulin peptide as one sharp mass peak in the spectrum of islets of both wild‐type and ZnT8 −/− mice, measured by in situ peptidomics 26 ; and (ii) the non‐crystallized guinea pig and coypu insulin would be more vulnerable to degradation, compared with human crystallized insulin 60,61 .…”
Section: Role Of Znt8 In Insulin Processing and Storage: Formation Ofmentioning
confidence: 99%
“…The precise subcellular localization and distribution of Zn 2ϩ in islets is also under debate. Histological data in fixed cells have shown mainly granular localization of Zn 2ϩ (27,28), whereas experiments with fractionation of islets have demonstrated that only 20 -30% of the total islet Zn 2ϩ was associated with the granular fraction (26,29). Given the significance of Zn 2ϩ for proinsulin biosynthesis and exocytosis, understanding the mechanisms of its uptake into islet cells is important.…”
Section: ؉mentioning
confidence: 99%
“…2 and total zinc contents shown in Table 1 that granular zinc (~30% of the islet zinc) under all culture conditions was sufficient to account for the 2-zinc-insulin hexamer as a storage form of granular insulin. 2 The possibility that ZINC, RELATIONSHIP TO INSULIN CONTENT OF ISLETS 881 complexes with a lower zinc to insulin ratio may exist in the rat /3 cell should not be excluded, particularly when considering the hazards of relating too closely quantification of zinc by atomic absorption with that of rat insulin by RIA. However, complexes with much higher zinc to insulin ratios, which can be produced in vitro (23), are not likely to exist in vivo because of the limited zinc content of the granule compartment.…”
Section: Endo • 1984 Volll5«no3mentioning
confidence: 98%
“…Results show that 1) zinc exists in a metabolically labile islet compartment(s) as well as in secretory granules; and 2) extragranular zinc, although not directly associated with insulin storage, may act as a reservoir for granular zinc and may regulate insulin synthesis, storage, and secretion in ways as yet unknown. (Endocrinology 115: [877][878][879][880][881]1984) E ARLY histological data suggested that 0-cell zinc is exclusively localized in the protein-insulin core of the secretory vesicle (1)(2)(3)(4). However, standard fixing and staining techniques may have removed less tightly bound zinc from either the granular or extragranular compartments (5).…”
mentioning
confidence: 97%